Baduanjin exercise in the treatment of hypertension: A systematic review and meta-analysis - Ma, Zhen; Lei, Honghui; Tian, Kexin; Liu, ZhiZe; Chen, Ying; Yang, Haoqi; Zhu, Xiangyu (Frontiers in Cardiovascular Medicine, 2022)
Background As a therapy to prevent and treat hypertension, exercise is widely used in clinical practice. But due to the lack of documentary evidence, Baduanjin as a relaxed and convenient mode of exercise is not currently recommended by professional health organizations to treat hypertension. The purpose of this article is to examine the efficacy of Baduanjin as an antihypertensive exercise therapy. Methods Our systematic retrieved of the entire relevant literatures in 12 databases. Finally, 28 eligible trials involving Baduanjin intervention in hypertension were included. After the quality assessment and bias risk assessment of the included trials, we analyzed the blood pressure values before and after the intervention, and performed meta-analysis on the random effect results. In order to explore the factors influencing the decrease of blood pressure, we also performed a subgroup analysis of the results. Results Participants (n = 2121) were adults (61.74 ± 5.85years of age, mean ± SD), with baseline blood pressure (systolic blood pressure (SBP) = 150.7 ± 9.2 mmHg, diastolic blood pressure (DBP) = 93.2 ± 8.8 mmHg). Baduanjin was practiced 7.5 ± 3.8 sessions / week for 28.2 ± 12.8 min /session for 16.7 ± 9.2 weeks. Overall, Baduanjin resulted in SBP (−9.3 mmHg, d = −1.49, 95%CI: −1.73 to −1.13) and DBP (−6.3 mmHg, d = −1.20, 95%CI: −1.51 to −0.88) vs. the control group (p < 0.001). After a subgroup analysis of age, we found that SBP heterogeneity was significantly reduced in the elderly group. Conclusion Our results indicate that Baduanjin can effectively reduce blood pressure (i.e., 9.3 mmHg and 6.3 mmHg of SBP and DBP reductions, respectively), and reduce the incidence rate of cardiovascular disease in hypertensive patients. In addition, we will be more likely to recommend that the elderly exercise Baduanjin.